Data supporting: 'The influence of augmented reality interaction design on Pilot's perceived workload and situation awareness' - Li, Wen-Chin; Zhang, Jingyi; Court, Samuel; Braithwaite, Graham; Kearney, Peter (Cranfield University, 2022)
This work explored the potential for Augmented Reality (AR) rendering information superimposed over the flight deck to increase a pilot€™s situation awareness (SA). This emerging technology introduced novel human-computer interaction paradigms that would have impact on pilot€™s cognitive demands.
Keywords: Augmented Reality'; 'Cognitive Demands'; 'Flight Deck Design'; 'Human-Computer Interaction'; 'Perceived Workload'